2016
DOI: 10.1016/j.mce.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal PCOS and PCOS-like phenotype on the offspring's health

Abstract: Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine disorder with both reproductive and metabolic abnormalities affecting women of reproductive age. While the exact origin of PCOS is unknown, observations from clinical and animal studies suggest that maternal hyperandrogenism may be a contributing factor. Because women with PCOS manifest hyperandrogenism during pregnancy, changes in the gestational endocrine milieu may play a role in the vertical transmission of this syndrome. This review discusses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 168 publications
(205 reference statements)
2
41
0
Order By: Relevance
“…From rodents [11–13] and sheep [14, 15] to NHPs [1618], animal studies overwhelmingly demonstrate how fetal T excess, and likely accompanying gestational hyperglycemia and hyperinsulinemia [2426], provide developmental origins for PCOS-like phenotypes. Experimental induction of T exposure in NHPs is achieved by daily injection of macaque dams with 10–15 mg T propionate (TP) during early-to-mid gestation.…”
Section: Hyperandrogenic Gestational Contributions To Pcos-like Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…From rodents [11–13] and sheep [14, 15] to NHPs [1618], animal studies overwhelmingly demonstrate how fetal T excess, and likely accompanying gestational hyperglycemia and hyperinsulinemia [2426], provide developmental origins for PCOS-like phenotypes. Experimental induction of T exposure in NHPs is achieved by daily injection of macaque dams with 10–15 mg T propionate (TP) during early-to-mid gestation.…”
Section: Hyperandrogenic Gestational Contributions To Pcos-like Traitsmentioning
confidence: 99%
“…Diagrammatic representation of gestational ages at fetal T exposure resulting in PCOS-like traits (blue boxes with T) in female mice and rats [11–13], sheep [14, 15] and rhesus monkeys [1618]. All gestational periods are aligned at mid-gestation.…”
Section: Fig (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the organizational effects of excess prenatal steroid hormone exposure in masculinizing the behavioral circuits in the males become only apparent during puberty when gonadal steroid output determines the expression of sex-typical behavior (Schulz et al 2009). This can be explained by the two-hit hypothesis, which states that an early-life adverse event (“first-hit”) programs a pathological condition that may be revealed only later in life by a subsequent exposure to an adverse influence or the so called “second hit” (Bayer et al 1999, Tang et al 2008, Puttabyatappa et al 2015). From an adverse exposure standpoint, humans are exposed throughout their lifespan to steroids involuntarily and sometimes unknowingly through food consumption (phytoestrogens), industrial byproducts (bisphenol A), diseases (CAH, PCOS), and/or voluntarily (contraception and anabolic steroids) (Bahrke et al 1998, Jefferson et al 2012, Pignatelli 2013, Peretz et al 2014, Jensen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to these paradoxcial interactions, a recent study found that a high‐fat diet mitigated the adverse effects of BPA on embryo implantation (Martinez et al ). In recent years it has become increasingly clear that the manifestation of a final phenotypic outcome is not merely dictated by the organizational changes that occur during critical periods of differentiation such as those induced by BPA in this study, but also is a function of the prevailing postnatal milieu (Puttabyatappa et al ). Additional studies addressing whether these unexpected findings in the BPA + OF group are adaptive or maladaptive would further our understanding of the interaction between prenatal BPA exposure and the postnatal environment in modulating cardiac function and identifying preventive treatment strategies.…”
Section: Discussionmentioning
confidence: 64%